1996
DOI: 10.1161/01.res.78.3.431
|View full text |Cite
|
Sign up to set email alerts
|

Differential Distribution of Electrophysiologically Distinct Myocytes in Conduit and Resistance Arteries Determines Their Response to Nitric Oxide and Hypoxia

Abstract: The cellular mechanisms that determine differences in reactivity of arteries of varying size and origin are unknown. We evaluated the hypothesis that there is diversity in the distribution of K+ channels between vascular smooth muscle (VSM) cells within a single segment of the pulmonary arteries (PAs) and that there are differences in the prevalence of these cell types between conduit and resistance arteries, which contribute to segmental differences in the vascular response to NO and hypoxia. Three types of V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
234
3
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 317 publications
(252 citation statements)
references
References 40 publications
13
234
3
2
Order By: Relevance
“…The present experiments operated on a peripheral portion of the pulmonary vascular bed where the arteries are mainly resistance arteries. As we did not ®nd any activity of K ATP channel openers, these results are consistent with those of Archer et al [26].…”
Section: Levcromakalimsupporting
confidence: 94%
See 1 more Smart Citation
“…The present experiments operated on a peripheral portion of the pulmonary vascular bed where the arteries are mainly resistance arteries. As we did not ®nd any activity of K ATP channel openers, these results are consistent with those of Archer et al [26].…”
Section: Levcromakalimsupporting
confidence: 94%
“…In conduit arteries, the calcium activated K + channels (K Ca channels) are predominant. No K ATP cell was identi®ed in resistance arteries which have a majority of voltage-gated potassium (K v ) channels [26]. Nine families of K v channels are recognized from cloning studies (K v1 ±K v9 ), each with subtypes.…”
Section: Levcromakalimmentioning
confidence: 99%
“…The pulmonary vasculature consists of large, elastic, extraparenchymal conduit pulmonary arteries (CPA, order 1 to 2) that arise from the sixth aortic arch and small, muscular resistance intrapulmonary arteries (RPA, ≥ 4th order), that originate from the mesenchymal lung bud by capillary plexus expansion [1]. This subdivision is associated with different response to several stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…While CPA dilates or fails to constrict to hypoxia, RPA is responsible for hypoxic pulmonary vasoconstriction, control the regional distribution of blood flow and largely determine pulmonary vascular resistance. This functional difference mainly depends on the distribution of electrophysiologically distinct myocytes in CPAs and RPAs arteries [1,2].Levosimendan is a positive inotropic agent (by increasing the sensitivity of troponin C to calcium) with vasodilating properties (by lowering of intracellular free Ca++, opening of different potassium channels and the inhibition of phosphodiesterase type III), also termed inodilator [3,4]. There are several animals studies in different acute pulmonary hypertension (PH) models secondary to thromboxane A2 infusion [5], endotoxemia [6], acute pulmonary embolism (PE) [7,8], and hypoxia [9] and some clinical studies that demonstrated the vasodilator effect of levosimendan on the pulmonary circulation, restoring right ventricular-arterial coupling as it increased right ventricular contractility concomitantly [10,11].…”
mentioning
confidence: 99%
“…1 Moreover, many vibrant "vascular villages" display rich diversity within a single vascular segment, with heterogeneity in SMCs that exist side by side. 2,3 The article by Pickering's group addresses the molecular mechanism underlying a form of SMC diversity that has morphological and functional aspects; namely the existence of synthetic versus contractile SMCs. 4 It is an important contribution because, in addressing their own hypothesis, they reveal a mechanism that has relevance to several unresolved questions in vascular biology.…”
mentioning
confidence: 99%